2015
DOI: 10.1103/physrevc.92.054614
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-channels description of multinucleon transfer and fusion reactions at energies near and far below the Coulomb barrier

Abstract: We investigate heavy-ion multinucleon transfer reactions using the coupled-channels formalism. We first use the semi-classical approximation and show that a direct coupling between the entrance and the pair transfer channels improves a fit to the experimental one-and two-neutron transfer cross sections for the 40 Ca+ 96 Zr and 60 Ni+ 116 Sn systems. We then discuss the validity of the perturbative approach and highlight the effect of high order terms. The effect of absorption is also investigated for energies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In conclusion, it was found that the two-neutron transfer probability is enhanced as compared to a simple expectation of independent particle transfer process, i.e., the square of oneneutron transfer probability. The coupled-channels calculations performed for this system also suggested a significant effect of the couplings to the collective excited states around the Coulomb barrier [75]. The TDHF + BCS formalism was also applied for this type of reactions [76,77].…”
Section: Nucleon-nucleon Correlationsmentioning
confidence: 99%
“…In conclusion, it was found that the two-neutron transfer probability is enhanced as compared to a simple expectation of independent particle transfer process, i.e., the square of oneneutron transfer probability. The coupled-channels calculations performed for this system also suggested a significant effect of the couplings to the collective excited states around the Coulomb barrier [75]. The TDHF + BCS formalism was also applied for this type of reactions [76,77].…”
Section: Nucleon-nucleon Correlationsmentioning
confidence: 99%
“…The importance of studying the reaction dynamics of colliding nuclei at energies near the Coulomb barrier lead the investigators to the barrier distribution function. For the barrier heights B and the corresponding weights D (B) from fusion cross section can be determined as the sum of the fusion cross section from distributed fusion barriers in form [28,32] ( ) ∫ ( ) ( ) ( )…”
Section: Fusion Barrier Distributionmentioning
confidence: 99%
“…While vibrational couplings usually lower the barrier, the effect of transfer channels is less clear despite sev-eral experimental investigations [4, 16-20, 89, 90]. One problem is the difficulty to incorporate transfer channels in coupled-channel calculations [91][92][93][94]. Alternatively, microscopic approaches can also be used to study transfer reaction mechanisms in heavy-ion collisions [95][96][97].…”
Section: Role Of Transfermentioning
confidence: 99%
“…One problem is the difficulty to incorporate transfer channels in coupled-channel calculations [91][92][93][94]. Alternatively, microscopic approaches can also be used to study transfer reaction mechanisms in heavy-ion collisions [95][96][97].…”
Section: Role Of Transfermentioning
confidence: 99%